Diversification of Type VI Secretion System Toxins Reveals Ancient Antagonism among Bee Gut Microbes - Margaret I. Steele (American Society for Microbiology, 2017)
ABSTRACT Microbial communities are shaped by interactions among their constituent members. Some Gram-negative bacteria employ type VI secretion systems (T6SSs) to inject protein toxins into neighboring cells. These interactions have been theorized to affect the composition of host-associated microbiomes, but the role of T6SSs in the evolution of gut communities is not well understood. We report the discovery of two T6SSs and numerous T6SS-associated Rhs toxins within the gut bacteria of honey bees and bumble bees. We sequenced the genomes of 28 strains of Snodgrassella alvi, a characteristic bee gut microbe, and found tremendous variability in their Rhs toxin complements: altogether, these strains appear to encode hundreds of unique toxins. Some toxins are shared with Gilliamella apicola, a coresident gut symbiont, implicating horizontal gene transfer as a source of toxin diversity in the bee gut. We use data from a transposon mutagenesis screen to identify toxins with antibacterial function in the bee gut and validate the function and specificity of a subset of these toxin and immunity genes in Escherichia coli. Using transcriptome sequencing, we demonstrate that S. alvi T6SSs and associated toxins are upregulated in the gut environment. We find that S. alvi Rhs loci have a conserved architecture, consistent with the C-terminal displacement model of toxin diversification, with Rhs toxins, toxin fragments, and cognate immunity genes that are expressed and confer strong fitness effects in vivo. Our findings of T6SS activity and Rhs toxin diversity suggest that T6SS-mediated competition may be an important driver of coevolution within the bee gut microbiota. IMPORTANCE The structure and composition of host-associated bacterial communities are of broad interest, because these communities affect host health. Bees have a simple, conserved gut microbiota, which provides an opportunity to explore interactions between species that have coevolved within their host over millions of years. This study examined the role of type VI secretion systems (T6SSs)—protein complexes used to deliver toxic proteins into bacterial competitors—within the bee gut microbiota. We identified two T6SSs and diverse T6SS-associated toxins in bacterial strains from bees. Expression of these genes is increased in bacteria in the bee gut, and toxin and immunity genes demonstrate antibacterial and protective functions, respectively, when expressed in Escherichia coli. Our results suggest that coevolution among bacterial species in the bee gut has favored toxin diversification and maintenance of T6SS machinery, and demonstrate the importance of antagonistic interactions within host-associated microbial communities.